DIAGNOSTIC TEST-BASED ASSESSMENT TOOL USING MOODLE TO MEASURE STUDENTS' METACOGNITIVE ABILITIES: Received: 10th January 2023; Revised: 3rd April 2023, 9th May 2023; Accepted: 11th May 2023 - Dewi, Novi Ratna; Savitri, Erna Noor; Listiaji, Prasetyo; Saputri, Luthfi Hanum; Dwijayanti, Ida (PUPIL: International Journal of Teaching, Education and Learning, 2023)
As part of mindset, metacognition is one of the key indicators of 21st century skills. In this 21st century learning era, the need for metacognitive assessment tools is very important. This study aims to measure students' metacognitive abilities on science concepts using a Moodle based self-diagnostic assessment and know the correlation between students' metacognitive abilities and their learning outcomes. The research used quantitative methods with a sample consisting of 2 classes of students taking Basic Science Courses Data analysis of students' metacognition level based on evaluation results and correlation analysis of students' metacognition skills and learning outcomes. The result indicated that diagnostic test-based assessment tool using Moodle can be used to measure students' science metacognition abilities. The results also showed a significant correlation between metacognitive abilities and student learning outcomes. Diagnostics test using Moodle can be an alternative metacognitive assessment of the learning process and an opportunity to create a 21st-century skills assessment.